Attitudes towards seeking mental health services among older adults: personal and contextual correlates - Kessler, Eva-Marie; Agines, Sabrina G.; Bowen, Catherine E. (Aging & mental health, 2015)
Objectives: Especially older adults underutilize professional mental health services. However, little is known about the factors associated with older adults’ attitudes towards seeking mental health services (ATSMHS). We therefore investigated a wide range of contextual (e.g. physical access, residence) and personal (e.g. perceived social support, life satisfaction, openness to experience) predictors of ATSMHS in a sample of older community-dwelling adults in Germany. We predicted that representations of old age as well as perceptions of (younger) psychotherapists would be uniquely important for determining ATSMHS.Method: A diverse sample of N = 156 older adults (Mage = 71.5 years, SD = 6.4, range: 60-92) completed questionnaire measures. We used hierarchical linear regression analyses to identify predictors of ATSMHS.Results: In the final saturated model, female gender, urban residence, personal and vicarious experience with psychotherapy, and higher perceived social support were each associated with more positive ATSMHS. In addition, more positive representations of old age and less negative perceptions of (younger) psychotherapists explained unique variance in ATSMHS over and above the other predictors. The overall model was significant and explained 49% of the variance in ATSMHS.Conclusion: Our findings can be used to inform interventions to improve older adults’ ATSMHS. Interventions that seek to improve older adults’ representations of their own aging as well as of psychotherapists may be useful for reducing the treatment gap.
Published online: 05 Jun 2014
Gesehen am 16.07.2020